Financial Development, Trade Openness, and Foreign Direct Investment: A Battle Between the Measures of Environmental Sustainability - Huo, Weidong; Ullah, Muhammad Rizwan; Zulfiqar, Muhammad; Parveen, Shahida; Kibria, Umar (Frontiers in Environmental Science, 2022)
Deterioration in the environmental quality is a major threat to the sustainable development of an economy as it results in serious economic problems and the researchers are conscious about the environment sustainability. They have identified several factors including financial development, inflow of foreign aid and openness of trade to promote environmental sustainability. Unfortunately, their findings remain inconclusive as they have imperfectly measured environmental sustainability. This study, thus, aims to contribute to the ongoing debate of environmental sustainability by testing the role of financial development, trade openness and foreign direct investment (FDI) in promoting environmental sustainability by using adjusted net savings as a measure of environmental sustainability. To do this, the study collects data from 1996 to 2019. The study uses financial development, trade openness and FDI as predictors while environmental sustainability as outcome variable. The study applies Auto Regressive Distributive Lag (ARDL) Methodology to analyze the impact. The findings show positive contributions of financial development, trade openness and foreign direct investment in promoting environment sustainability. We suggest encouraging trade through lower-taxation programs and increasing competition in the financial markets through privatization and domestic and international liberalization to stimulate environmental sustainability. We also recommend imposing high taxes and penalties on such activities that damage the quality of environment.